Implementation Of Role Playing Method In The Hygiene Hadith Learning Toward Early Children’s Healthy Behavior Of Group B In Dabin Aggrek Gunungpati Semarang - Wijayanti, Nira Arum (Jurusan PGPAUD FIP UNNES, 2017)
The behavior of healthy life is associated with someone’s effort to preserve, maintain and improve their health. The hadits learning in RA Dabin Anggrek, thereis hadith about cleanliness that reflects the child’s healty life behaviour. However, there are still many children who do not behave according to the hadith. Therefore, it takes an interesting learning methods. One of these methods is role playing, through this method children can practice healthy behavior directly, so it would be impressed on children. This study aims to determine the differences in health behavior of children before and after treatment, as well as knowing the differences in health behavior of children between the control group and the experimental group. The research method that is used is experimental. The research design that wast aken is Quasi Experimental Design with this type of Nonequivalent Control Group Design.The population in this study are all children of group B in Dabin Mawar, with 36 children for sample consists of 18 children from RA Miftahul Hidayah (experimental group) and 18 children from RA Nurul Huda (control group). The results obtained from the experimental group had Sig (2-tailed) of 0.000 < 0.05. It means that the results of the pretest and posttest has significant difference. On the other hand, the control group had Sig (2-tailed) 0.120 > 0.05. It means that the pretest and posttest are relatively similar. After being given the treatment, the experimental group had result Sig(2 tailed) of 0.000 < 0.05. It means that there are significant differences in both of groups. Based on these descriptions, it can be concluded that the method of playing a role in learning hadith of cleanliness can increase the healthy behaviors in children in group B Dabin Mawar Gunungpati Semarang.